SIMULATION AND OPTIMIZATION OF ULTRALIGHT HELICOPTER AERODYNAMIC CHARACTERISTICS - Viktor P. Zharov; Sergey P. Lisin (Advanced Engineering Research)
The simulation and optimization of the ultralight helicopter aerodynamic characteristics at the design stages and phases which permit to determine optimal values of the engine power and speed are performed.